The promising role of DECT in the diagnosis of Osteitis Condensans Ilii: a case report - Testini, Valentina; Eusebi, Laura; Guerra, Francesco Saverio; Manantrizio, Domenico; Guglielmi, Giuseppe (Acta Biomedica Atenei Parmensis, 2023)
Osteitis condensans ilii (OCI) is a noninflammatory condition of no clear etiology, cause of axial low back pain. It is characterized by sclerotic bone lesions at the iliac region of the sacroiliac joints. The diagnosis is based on radiological findings and the exclusion of other conditions associated with back pain. We present a case of bilateral OCI in a young woman with bone sclerosis at sacroiliac joints diagnosed with the use of Dual Energy CT.